Development and preliminary validation of a post-fistula repair reintegration instrument among Ugandan women - Alison El Ayadi; Hadija Nalubwama; Justus Barageine; Torsten B. Neilands; Susan Obore; Josaphat Byamugisha; Othman Kakaire; Haruna Mwanje; Abner Korn; Felicia Lester; Suellen Miller (BMC, 2017)
Abstract Background Obstetric fistula is a debilitating and traumatic birth injury affecting 2-3 million women globally, mostly in sub-Saharan Africa and Asia. Affected women suffer physically, psychologically and socioeconomically. International efforts have increased access to surgical treatment, yet attention to a holistic outcome of post-surgical rehabilitation is nascent. We sought to develop and pilot test a measurement instrument to assess post-surgical family and community reintegration. Methods We conducted an exploratory sequential mixed-methods study, beginning with 16 in-depth interviews and four focus group discussions with 17 women who underwent fistula surgery within two previous years to inform measure development. The draft instrument was validated in a longitudinal cohort of 60 women recovering from fistula surgery. Qualitative data were analyzed through thematic analysis. Socio-demographic characteristics were described using one-way frequency tables. We used exploratory factor analysis to determine the latent structure of the scale, then tested the fit of a single higher-order latent factor. We evaluated internal consistency and temporal stability reliability through Raykov's ρ and Pearson's correlation coefficient, respectively. We estimated a series of linear regression models to explore associations between the standardized reintegration measure and validated scales representing theoretically related constructs. Results Themes central to women's experiences following surgery included resuming mobility, increasing social interaction, improved self-esteem, reduction of internalized stigma, resuming work, meeting their own needs and the needs of dependents, meeting other expected and desired roles, and negotiating larger life issues. We expanded the Return to Normal Living Index to reflect these themes. Exploratory factor analysis suggested a four-factor structure, titled 'Mobility and social engagement', 'Meeting family needs', 'Comfort with relationships', and 'General life satisfaction', and goodness of fit statistics supported a higher-order latent variable of 'Reintegration.' Reintegration score correlated significantly with quality of life, depression, self-esteem, stigma, and social support in theoretically expected directions. Conclusion As more women undergo surgical treatment for obstetric fistula, attention to the post-repair period is imperative. This preliminary validation of a reintegration instrument represents a first step toward improving measurement of post-surgical reintegration and has important implications for the evidence base of post-surgical reintegration epidemiology and the development and evaluation of fistula programming.